A novel optimal design approach for bladeless wind turbines considering mechanical properties of composite materials used - Zeinab Mohamed; Moataz Soliman; Mohamed Feteha; E. Saber (Scientific Reports)
Abstract Bladeless wind turbines face operational limitations due to the lock-in phenomenon. This study introduces two novel mechanisms for designing bladeless wind turbines to address this issue, enabling operation across a broad wind speed range from 2 to 10 m/s while ensuring that lock-in conditions are satisfied at any wind speed within this range. The study aims to maintain optimal performance without any decline that is observed in conventional bladeless wind turbines by controlling the turbine’s natural frequency through implementing these mechanisms, either by adjusting the effective length of the stand or by incorporating an additional mass in the hollow mast, or both. A mathematical model including dynamic analysis is constructed to adjust natural frequency to match the shedding frequency at the specified wind speed. Validation of our model shows high accuracy. Numerical results demonstrate that applying these mechanisms ensures the turbine is optimally designed across varying parameters. Findings reveal that for lower flexural modulus values, the first mechanism alone can achieve a 99.2% increase in mechanical efficiency at 7 m/s. For higher flexural modulus values, incorporating the second mechanism is essential to reduce the turbine’s overall size. This integrated approach improves efficiency with a 55.7% increase.